Experimental investigations on spray characteristics in twin-fluid atomizer - Pipatpong Watanawanyoo (2018)
A twin-fluid atomizer was designed and developed for fuel atomization. The droplet characteristic in the spray which was produced with the atomizer was investigated experimentally. Air flow induced in the atomizer causes a pressure reduction, hence the fuel is sucked into the atomizer. The mixture flow of air and liquid caused the atomization downstream due to the turbulence. In the twin-fluid atomizer, atomization is attained by injecting an air stream at tip of the liquid inlet port. In this research, the test liquid supply pressure was kept constant and the air flow rate through the atomizer was varied over a range of air supply pressure to obtain the variation in air liquid mass flow ratio (ALR) from 0.2 to 2.7. The results revealed that the air assisted atomizer had a capability to inject the test liquid in the range of the rates of 0.0019-0.00426 kg/s, with the use of air pressure supplied from 68.9 to 689 kPa. The images of the spray were obtained with a shadowgraph technique and analyzed to obtain the particle size and its distribution. Droplet size from twin-fluid atomizer had various sizes in the range of about 17-200 μm. The atomizer can be applied for aerosol and combustion purposes. © 2011 Published by Elsevier Ltd.